Post-Tolerance Of The Roemah Bhinneka In Dynamic Of Indonesian Pluralism - Rohman, Angga Nur; Basir, Abdul; Lubis, Abdul Rojak; Qona’ati, Arini Fahma; Aziz, Moh. Ali (AL-ADYAN, 2025)
Post-tolerance is a concrete form of behavior in appreciating and respecting each other among religious communities. This is particularly necessary in a diverse country like Indonesia to foster diversity. Roemah Bhinneka is a post-tolerance phenomenon in Surabaya that operates in the field of social diversity among religions. They collaborate by combining one religious activity with another, such as opening prayers by Muslims for Christmas and New Year celebrations in churches. The purpose of this study is to describe the phenomenon of post-tolerance at Roemah Bhinneka in Indonesia with its diverse society. This research uses a qualitative approach with a case study type, Emiel Durkheim's theory of organic solidarity, and data collection through interviews and documentation. The results of this study show that post-tolerance takes the form of involvement in other religious activities, such as joint prayer, social activities, and interfaith discussions. Differences in understanding and beliefs are united by a single vision of a social movement for diversity to build peace and justice in Indonesia's multicultural society. They dare to build arguments for coexisting with other religions through discussion and joint religious practices. From the perspective of organic solidarity theory, Roemah Bhinneka's practice of post-tolerance can be an important contribution to building an Indonesian society that is mutually involved in various social and religious activities across beliefs. Keywords: Religion, Roemah Bhinneka, Pluralism, Post-Tolerance,